2020
DOI: 10.1002/ags3.12340
|View full text |Cite
|
Sign up to set email alerts
|

Is remnant pancreatic cancer after pancreatic resection more frequent in early‐stage pancreatic cancer than in advanced‐stage cancer?

Abstract: Aim As the prognosis of patients who undergo resection for pancreatic cancer has improved, reports of remnant pancreatic cancer after pancreatic cancer resection have been increasing. Previous studies regarding early‐stage pancreatic cancer showed a high incidence of remnant pancreatic cancer in these patients. The aim of this study was to investigate the incidence of remnant pancreatic cancer according to the degree of progression of the initial pancreatic cancer. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The feasibility and usefulness of remnant pancreatic resection has been reported in several retrospective studies [3,4,[10][11][12], and our results were consistent with these reports. Our data showed that remnant pancreatic resection was more frequent in early-stage pancreatic cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The feasibility and usefulness of remnant pancreatic resection has been reported in several retrospective studies [3,4,[10][11][12], and our results were consistent with these reports. Our data showed that remnant pancreatic resection was more frequent in early-stage pancreatic cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Ikemoto et al [13] and Kanno et al [14] reported that patients with early-stage pancreatic cancer (stage 0-I) showed a high incidence of remnant pancreatic cancer. However, Miyasaka et al [10] reported that the potential for developing remnant pancreatic cancer was comparable between early-stage and the advanced-stage groups. Yamada et al [4] also reported that the short distance from the pancreatic stump (less than 10 mm) could be a prognostic factor for local recurrence after pancreatic resection.…”
Section: Discussionmentioning
confidence: 98%
“…Miyasaka et al reported that remnant pancreatic cancer developed more frequently after the resection of cancer in the pancreatic body-tail. 53 Makohon-Moore et al revealed that precancerous neoplastic cells, such as PanINs, can move through the pancreatic ductal system and progress into PDAC with the accumulation of genetic and epigenetic changes. 54 Furthermore, initial PDACderived sEVs, which flow through the pancreatic duct from the body-tail to the head, could initiate the development of remnant PDAC through cell-to-cell communication.…”
Section: Pj-derived Sevs As a Potential Therapeutic Target For Pdacmentioning
confidence: 99%
“…Miyasaka et al. reported that remnant pancreatic cancer developed more frequently after the resection of cancer in the pancreatic body‐tail 53 . Makohon–Moore et al.…”
Section: Characteristics Of Pancreatic Juice‐derived Sevs and Their P...mentioning
confidence: 99%
“…Surgery remains the main curative treatment for pancreatic cancer, and sometimes, repeat resection is needed for recurrence. Recently, total pancreatectomy including remnant pancreatic resection has been aggressively performed [3] , [4] . Improvement with surgery and powerful combination chemotherapy often dramatically decreases the extension of pancreatic tumours [5] .…”
Section: Introductionmentioning
confidence: 99%